ROESY and 13C NMR to distinguish between d- and l-rhamnose in the α-d-Manp-(1 → 4)-β-Rhap-(1 → 3) repeating motif. Issue 14 (25th March 2022) - Davidson, Jeffrey; Gauthier-Signore, Charles; Bishop, Kevin P.; Wicks, Christopher; Monteiro, Mario A.; Roy, Pierre-Nicholas; Auzanneau, France-Isabelle
Abstract : CH3 -6 of l -Rha and H-2 of d -Man give ROE correlation in the α-d -Man p -(1 → 4)-l -Rha p motif. C-2 in d -Man is shifted upfield in the 13 C NMR spectrum of the β-d -Rha p -(1 → 3)-d -Man p motif. Abstract : Many children suffering from autism spectrum disorder (ASD) experience gastrointestinal (GI) conditions. Enterocloster bolteae has been regularly detected in the stool of individuals suffering from GI symptoms and autism. Literature has suggested that E. bolteae strains WAL 16351 and WAL 14578 produce an immunogenic capsular polysaccharide (CPS) comprised of disaccharide repeating units: α-d -Man-(1 → 4)-β-Rha-(1 → 3) that could be used for the development of an immunotherapeutic vaccine. Ambiguity in the configuration of rhamnose led to the synthesis of tri- and disaccharide analogues containing d -rhamnose and l -rhamnose, respectively. ROESY-NMR spectra showed that CH3 -6 of rhamnose and H-2 of mannose in the l -Rha containing disaccharide gave correlation. No such correlation was seen between the CH3 -6 of rhamnose and the H-2 of mannose in the d -Rha containing trisaccharide. Molecular dynamics studies on hexasaccharide containing l -Rha or d -Rha confirmed that these structures adopt conformations resulting in different distances between the C6-rhamnose and the H-2 mannose of the preceding residue. We also demonstrate that assignment of the absolute configuration of the rhamnosyl residue in the β-Rha p -(1 → 3)-d -Man linkage can be determined using the 13 C chemical shift of C-2 in of d -Mannose. While β-d -Rha will lead to an upfield shift of C-2 due to γ- gauche interaction between H-1 Rha and H-2 Man, β-l -Rha will not. Our results provide insights to distinguish between d - and l -rhamnose in the α-d -Man p -(1 → 4)-β-Rha p -(1 → 3) repeating motif.